Influence of water security and its’ consumption on the health of market women in Oyo township, Nigeria - Olanrewaju, Oniyangi, Shuaib; Olaniy, Fagbamila, Sayofunmi; Anike, Adebowale, Grace; Ayodeji, Falusi, Bamidele; Omolara, Oyawole, Dorcas (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The influence of water security and its’ consumption on the health of market women in Oyo township, Nigeria was investigated in this study. A descriptive research survey was adopted and the population of the study comprised of all market women in Oyo township, Nigeria. Simple random and convenient sampling technique was used to select two markets and four hundred (400) respondents. Structured questionnaire was used for data collection. Pearson Product Moment Correlation was used for data analysis. A correlation coefficient of 0.73 was obtained. Four postulated hypotheses were tested using inferential statistics of chisquare (X2 ) at 0.05 alpha levels. Results obtained showed that water security; volume of water consumed; water storage and water purification had significant influence on health of market women. We therefore recommended that market women should be adequately educated on the importance of water security and purification in order to guarantee better healthy living.